El pluricentrismo de la cultura lingüística hispánica: política lingüística, los estándares regionales y la cuestión de su codificación - Greußlich, Sebastian (2015)
Approximately over the past ten years, the RAE and its associated Academies have published several works committed explicitly to a pluricentric vision of Hispanic language culture. This paper aims at examining the impact of pluricentrism — a key concept in terms of current language policy — on the conceptualization of linguistic variation and, consequently, the treatment of empirical data. In doing so, the focus will be on the Nueva gramática de la lengua española (from here “NGLE”), where this problematic interrelation is reflected in an especially complex way.